Knowledge and perceptions about Covid-19 in the marginalized population of southeastern Mexico - José A De Fuentes-Vicente; Nancy L Hernández-Reyes; Flor M Bermúdez-Urbina; Sergio Meneses-Navarro; Ana L Castillo-Hernández; Nancy G Santos-Hernández; Javier Gutiérrez-Jiménez; Alex Córdoba-Aguilar (Instituto Nacional de Salud Pública, 2021)
Not available